2022
DOI: 10.1007/s12325-022-02274-3
|View full text |Cite|
|
Sign up to set email alerts
|

Sublingual Dexmedetomidine for Agitation Associated with Schizophrenia or Bipolar Disorder: A Post Hoc Analysis of Number Needed to Treat, Number Needed to Harm, and Likelihood to be Helped or Harmed

Abstract: Introduction:The objective was to use the evidence-based medicine metrics of number needed to treat, number needed to harm, and likelihood to be helped or harmed to appraise the clinical efficacy and tolerability of sublingual dexmedetomidine in adults with agitation associated with schizophrenia or bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In emergency situations where an injectable antipsychotic is indicated (e.g., for a highly agitated patient), an anticholinergic medication is often administered in combination with an antipsychotic and benzodiazepine for rapid control [ 49 ]. Alternative approaches for the emergency treatment of agitation include an injectable SGA that has reduced risk of dystonia (e.g., olanzapine, ziprasidone) or sublingual dexmedetomidine [ 50 , 51 ].…”
Section: Differentiation Of Drug-induced Movement Disorders and Their...mentioning
confidence: 99%
“…In emergency situations where an injectable antipsychotic is indicated (e.g., for a highly agitated patient), an anticholinergic medication is often administered in combination with an antipsychotic and benzodiazepine for rapid control [ 49 ]. Alternative approaches for the emergency treatment of agitation include an injectable SGA that has reduced risk of dystonia (e.g., olanzapine, ziprasidone) or sublingual dexmedetomidine [ 50 , 51 ].…”
Section: Differentiation Of Drug-induced Movement Disorders and Their...mentioning
confidence: 99%
“…49,50 A post hoc analysis of combined study results reported the NNT for response versus placebo was 3 (95% CI, 3-3). 51 Across both studies, the most common adverse reactions (incidence ≥ 5% and at least twice the rate of placebo) are somnolence (23% for the 180-µg group, 22% for the 120-µg group, 6% with placebo), oral paresthesia or oral hypoesthesia (7%, 6%, 1%), dizziness (6%, 4%, 1%), dry mouth (4%, 7%, 1%), hypotension (5%, 5%, 0%), and orthostatic hypotension (5%, 3%, <1%). 24 The cost of a dose of sublingual dexmedetomidine is higher than alternative IM formulations, which may impact uptake.…”
Section: Citrome Et Almentioning
confidence: 99%
“…A post hoc analysis of the two phase 3 trials with sublingual dexmedetomidine was conducted to calculate the numbers needed to treat (NNT), numbers needed to harm (NNH), and likelihood to be helped or harmed (LHH) [ 17 ]. The NNT was calculated based on the PEC response rate defined as a 40% or greater reduction in PEC score from baseline.…”
Section: Post Hoc Analysismentioning
confidence: 99%